A simulation analysis of the longer-term effects of immigration on per capita income in an aging population - Frank T. Denton; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2015)
Immigration is a possible instrument for offsetting longer-run adverse effects of population aging on per capita income. Our "laboratory" is a fictional country Alpha to which we assign demographic characteristics typical of a country experiencing population aging. Simulations indicate that a very high immigration rate with heavy concentration in younger working ages might be required to keep per capita income from declining. More rapid productivity growth would also offset population aging as would higher rates of labour participation of older people. Longer life expectancy, taken alone, would lower per capita real income, as would higher fertility rates.
Keywords: J10; J11; J18; 330; immigration; per capita income; population aging; age structure; simulation